Tax policy reforms in Nigeria - Ayodele Odusola (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Nigeria is governed by a federal system, hence its fiscal operations also adhere to the same principle, a fact which has serious implications on how the tax system is managed. The country's tax system is lopsided, and dominated by oil revenue. It is also characterized by unnecessarily complex, distortionary and largely inequitable taxation laws that have limited application in the informal sector that dominates the economy. The primary objective of this paper is to prepare a case study on tax policy reforms in Nigeria, with the specific objectives of examining the main tax reforms in the country; highlighting tax revenue profile and composition; analysing possible distributional impacts on the poor; discussing major problems that could prevent effective tax implementation in the country; and offering suggestions for reforms.
Keywords: E62; H20; 330; tax reform; Nigeria; administration; Steuerpolitik; Steuerreform; Nigeria